Family Support Relationship in Reducing Pre op Anxiety in the Operating Room of TK II Hospital 17.05.01 Marthen Indey Jayapura - Hormat Janner Manurung; Achmad Alfian Ingkir (Oshada, 2025)
Pre-operative anxiety can affect the patient's psychological and physical condition before undergoing surgery. This study aims to test the hypothesis that family support has a significant influence in reducing patient anxiety. Quantitative research methods with a cross-sectional design were used to analyze data obtained from patient samples at TK II Hospital 17.05.01 MARTHEN INDEY JAYAPURA. The results of the analysis showed a significant negative correlation between family support and the patient's anxiety level. The higher the level of family support the patient feels, the lower the level of anxiety they experience. These findings provide support for the important role of the family in providing emotional support to patients before surgery. The implication of this research is the need for integration of family support in pre-operative patient care protocols as well as the development of educational programs for families on how to provide effective support.To identify and analyze patients in family support relationships in reducing pre-op anxiety in the operating room at Rs Tk Ii 17.05.01 Marthen Indey Jayapura.The research used was cross sectional with a Likert scale questionnaire method which was declared valid and reliable to find the relationship between family support as an independent variable and the patient's anxiety level in the operating room at Marthen Indey Hospital as the dependent variable. Researchers also explain disturbing factors that can influence the dependent variable. The number of participants used was 32 participants.The results of this study show that there is a significant relationship between family support and the level of pre-operative anxiety in patients who will undergo surgery. The higher the level of family support felt by the patient, the lower the level of anxiety experienced before surgery.The results of this study indicate a significant relationship between family support and pre-operative anxiety levels in patients in the operating room. The higher the support provided by the family, the lower the level of anxiety experienced by the patient.